CDK1 mediates the metabolic regulation of DNA double-strand break repair in metaphase II oocytes - Tian-Jin Xia; Feng-Yun Xie; Juan Chen; Xiao-Guohui Zhang; Sen Li; Qing-Yuan Sun; Qin Zhang; Shen Yin; Xiang-Hong Ou; Jun-Yu Ma (BMC Biology)
Abstract Background During oocyte maturation, DNA double-strand breaks (DSBs) can decrease oocyte quality or cause mutations. How DSBs are repaired in dividing oocytes and which factors influence DSB repair are not well understood. Results By analyzing DSB repair pathways in oocytes at different stages, we found that break-induced replication (BIR) and RAD51-mediated homology-directed repair (HDR) were highly active in germinal vesicle breakdown (GVBD) oocytes but suppressed in metaphase II (MII) oocytes and the BIR in oocytes was promoted by CDK1 activity. By culturing oocytes in different media, we found that high-energy media, such as DMEM, decreased CDK1 protein levels and suppressed BIR or HDR in MII oocytes. In contrast, 53BP1-mediated nonhomologous end joining (NHEJ) repair was inhibited in germinal vesicle (GV) and GVBD oocytes but promoted in MII oocytes, and NHEJ was not affected by DMEM medium and CDK1 activity. In addition, in DSB MII oocytes, polymerase theta-mediated end joining (TMEJ) was found to be suppressed by CDK1 activity and promoted by high-energy media. Conclusions In summary, MII oocytes exhibit high heterogeneity in DSB repair, which is regulated by both metabolic factors and CDK1 activity. These results not only expand our understanding of oocyte DSB repair but also contribute to the modification of in vitro maturation medium for oocytes.